Managing public health spending growth: Public’s views - Araújo, N.; Reis, A.; Borges, A. P.; Rosa, A. (Journal of Health Management, 2023)
The need to guarantee public health spending sustainability remains on the governments’ agenda, despite constant efforts to improve health sector efficiency and to contain health spending growth. In this paper, we analyse citizens’, managers’ and health professionals’ views concerning the choice of alternative National Health Service (NHS)’ financing sources and the selection of priority areas to be financed from public funds. The main novelty of this study is the auscultation and the evaluation of different stakeholders’ perspectives concerning health spending decisions, namely, health professionals, managers and the general public. An online questionnaire was used to collect data. Methods include descriptive and inferential statistics, a Pareto graph and a factorial analysis. Our results reveal the preferable additional NHS funding sources are lottery and games of chance and the increase in alcohol and tobacco taxes. The respondents defend that priorities should consider the improvement of the population’s health status, namely, considering the universality of access, equity, effectiveness and efficiency, in line with the NHS’ mission. Health professionals are also concerned about disease prevention and health promotion. This paper contributes empirical evidence to support health manager decisions, focusing on rationing decisions and alternative financing sources.